2021
DOI: 10.1136/bcr-2021-243083
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive management of acute pulmonary embolism in primary care using telemedicine in the COVID-era

Abstract: A healthy, active woman in her 70s reported intermittent exertional dyspnoea for 2 months, notable during frequent open-water swimming. Symptoms were similar to an episode of travel-provoked pulmonary embolism 3 years prior. She denied chest pain, cough, fever, extremity complaints and symptoms at rest. Due to the COVID-19 pandemic, her healthcare system was using secure telemedicine to evaluate non-critical complaints. During the initial video visit, she appeared well, conversing normally without laboured bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Moreover, after COVID-19 pandemic, there is a trend to implement telemedicine as an expanding and feasible approach to improve medical care for patients with chronic diseases. 24–26 These advances have the potential to support patients with long-term diseases to manage their health at home, leading a remote healthcare more accessible and efficient. 26 Two earlier studies found usefulness of phone-based patients follow-up, 8 16 although our work analysed the impact of this strategy comparing patients diagnosed of CTEPH before and after applying the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after COVID-19 pandemic, there is a trend to implement telemedicine as an expanding and feasible approach to improve medical care for patients with chronic diseases. 24–26 These advances have the potential to support patients with long-term diseases to manage their health at home, leading a remote healthcare more accessible and efficient. 26 Two earlier studies found usefulness of phone-based patients follow-up, 8 16 although our work analysed the impact of this strategy comparing patients diagnosed of CTEPH before and after applying the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as stated above, published literature indicates that insurance is only one contributor to life expectancymany economic, lifestyle, and social factors also influence life expectancy outcomes. 22,[39][40][41][42][43] Furthermore, many of these factors influence insurance status. Thus, members of KPMAS examined in this study were likely to benefit from other socioeconomic and lifestyle advantages that could improve their life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…The research team met weekly during data analysis to develop the codebook and review emergent themes. Research team members who conducted the interviews discussed codes and themes to reach consensus on code meanings and domains, [42][43][44] co-creating the structure of the analysis and establishing trustworthiness. 45 The finalized codebook was then used to code all transcripts.…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine has also become a key tool for screening potentially early symptoms of Sars-Cov-2, protecting both the patients and medical personnel from additional contamination exposure (Hollander and Carr, 2020;Perrin et al, 2020). Many scholars have recently reported a revolution of telemedicine in various healthcare areas, including, inter alia, in pulmonology and primary care (Chang et al, 2021); oncology (Hasson et al, 2021), otolaryngology (Ohlstein et al, 2020).…”
Section: Conversion Of Sars-cov-2 Threats Into Business Opportunities By Polish Outpatient Clinics 904mentioning
confidence: 99%